2010
DOI: 10.1037/a0017763
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an early literacy professional development intervention on head start teachers and children.

Abstract: Effects of a 1-semester professional development (PD) intervention that included expert coaching with Head Start teachers were investigated in a randomized controlled trial with 88 teachers and 759 children. Differential effects of technologically mediated (remote) versus in-person (on-site) delivery of individualized coaching with teachers also were examined in a random assignment design. Hierarchical linear model analyses revealed positive PD intervention effects on general classroom environment (d ϭ 0.99) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
227
2
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(250 citation statements)
references
References 32 publications
16
227
2
5
Order By: Relevance
“…Most research has yielded disappointing results with regards to the effectiveness of PD in helping teachers improve their knowledge and instructional practices (e.g., Garet et al, 2008;Garet et al, 2011;O'Dwyer et al, 2010;Powell, Diamond, Burchinal, & Koehler, 2010). Results are even more disappointing regarding impact on student learning and achievement (e.g., Garet et al, 2008Garet et al, , 2011O'Dwyer et al, 2010;Powell et al, 2010).…”
Section: On the Effectiveness Of Teacher Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research has yielded disappointing results with regards to the effectiveness of PD in helping teachers improve their knowledge and instructional practices (e.g., Garet et al, 2008;Garet et al, 2011;O'Dwyer et al, 2010;Powell, Diamond, Burchinal, & Koehler, 2010). Results are even more disappointing regarding impact on student learning and achievement (e.g., Garet et al, 2008Garet et al, , 2011O'Dwyer et al, 2010;Powell et al, 2010).…”
Section: On the Effectiveness Of Teacher Pdmentioning
confidence: 99%
“…Most research has yielded disappointing results with regards to the effectiveness of PD in helping teachers improve their knowledge and instructional practices (e.g., Garet et al, 2008;Garet et al, 2011;O'Dwyer et al, 2010;Powell, Diamond, Burchinal, & Koehler, 2010). Results are even more disappointing regarding impact on student learning and achievement (e.g., Garet et al, 2008Garet et al, , 2011O'Dwyer et al, 2010;Powell et al, 2010). Every year, governments around the world invest astronomical amounts of money on traditional PD activities such as seminars, talks, workshops, and conferences (Gersten, Dimino, Jayanthi, Kim, & Santoro, 2010;Yoon, Duncan, Lee, Scarloss, & Shapley, 2007), brief and sporadic events in which teachers tend to be passive recipients of information, having no opportunities to collaborate with others.…”
Section: On the Effectiveness Of Teacher Pdmentioning
confidence: 99%
“…Supervisory coaching has been found to increase the accuracy of teacher implementation of academic instruction. Powell, Diamond, Burchinal, and Koehler (2010) used a Hierarchical Linear Model to examine the effects of literacy-focused professional development using expert coaching and to determine whether or not there are differential effects of remote versus on-site delivery of coaching. The study included 759 students enrolled in 88 classrooms in 24 Head Start centers in 11 counties in a midwest state.…”
Section: Research On Supervisory Coachingmentioning
confidence: 99%
“…Research has shown that supervisory coaching is effective for improving fidelity of academic and behavioral instruction. A number of recommendations for future research arise from the literature regarding supervisory coaching including (a) the need for research to determine if a particular type of coaching is more effective than another (Powell et al, 2010), (b) the implementation of supervisory coaching using natural implementers rather than researchers (Myers et al, 2011), (c) research in a wider range of settings and with a wider range of participants (Myers et al, 2011), (d) additional research examining student data in addition to teacher data (Myers et al, 2011), (e) research to examine the level of intensity of teacher support needed to make sufficient gains in teacher behavior (Janssen et al, 2010), and (f) the appropriate and effective use of technology in the coaching process (Powell et al, 2010).…”
Section: Research On Supervisory Coachingmentioning
confidence: 99%
“…A rationale for focusing this study solely on classroom processes, independent of student outcomes, is suggested by the results of a number of studies showing that teachers may provide only limited supports to children with respect to development of lower-and higher-level language skills, particularly within the pre-K setting (Jackson et al, 2006;Pence, Justice, & Wiggins, 2008;Pentimonti & Justice, 2010;Powell, Diamond, Burchinal, & Koehler, 2010). …”
Section: Improving Language-focused Comprehension Instruction In Primmentioning
confidence: 99%